Pemanfaatan Digital Marketing dalam Pemasaran Briket Arang dari Sekam Padi di Desa Pangkoh Hulu, Kalimantan Tengah - Silvani Permatasari; Muhammad Aldri; Jhon Paris Pasaribu; Nabila Putri Aditya; Theressia Angel Lady Saragih; Natalia Resoldes LBN Tobing; Yenisa Jestin Ganindyatama; Masaris; Rahmidiati; Andreyan Cesarianto; Indah Noniika (Jurnal Pengabdian Kampus, 2022)
The higher the production produced in agriculture, the higher the waste generated. For example, such as rice, the waste produced is very large, namely rice husks. Rice husk that can be utilized and developed for fuel needs. The method used was preparation, socialization and training which was carried out in Pangkoh Hulu Village, Pandih Batu District, Pulang Pisau Regency, Central Kalimantan. Charcoal briquettes are made from rice husks that are burned, mashed, and filtered until clean then mixed with tapioca flour and water, after which the briquettes are molded and dried to harden for 3-5 days. Digital marketing training in the form of packaging and branding is carried out to obtain added value so that it can be marketed by local residents. The participants who attended were the surrounding community, PKK women, and the X 2022 National Community Service Program students. There were approximately 30 participants who attended the activity and the Pangkoh Hulu Village community received and welcomed the training that we carried out. Making rice husk charcoal briquettes is one way to process rice husk waste so that it can become a selling point that can be marketed.